Thermostable, reusable, waterproof, and breathable PTFE coated PAI nanofiber membrane for protective application; The Journal of The Textile Institute; Vol. XX, iss. X - Yuan Wang; Mingle Ding; Fei Wang; Surmenev R. A. Roman Anatolievich; Xiaoyan Liu; Jianyong Yu; Bin Ding (2025, 2025)
Title screen